O aprendizado e resistência camponesa nos acampamentos e assentamentos de sem-terra em Quedas do Iguaçu/PR - Roos, Djoni (2010)
The social movements, mainly the MST, possess prominence in the process of fight of the peasants in Brazil. By means of the movements, the peasants have reached a set of conquests of which if he detaches the nesting land. But, in the trajectory of fight of the peasants in the social movements diverse contradictions, conflicts and actions of internal resistances exist that go in contrast to definitive practical conceptions and of the proper movements. The conflicts and internal resistances appear because the leaderships of the movements direct strange actions to the project of the peasants, as the collective cooperatives, for example. Thus, the fight for the land is formed by incompatible actions that possess origin in the encampments and if they reveal with more intensity in the nestings, when the peasants conquers greater autonomy. In this process of fight still, a learning exists politician constructed and acquired during the period of the encampment that later is materialized in the nestings. At the same time, this learning intercrosses with a learning and to know constructed in the trajectory of life of the peasants, that is, exists a learning forged in the process of fight in the social movements and learning, also forged in the fights and resistances, is of the movements, that however if complement and however oppose. To understand this learning in the movements, as well as the existing conflict of projects in the fight for the land, two nestings in the city of Quedas do Iguaçu (region Center-South of the State of the Paraná), being one older, nesting had been studied Rio Perdido, created in 1988 and formed for 60 families and the other, the Celso Furtado, created in 2005, and formed for 1089 families. Both the nestings had been conquered from fights made in the MST.